HUBUNGAN TINGKAT KECACATAN DAN TINGKAT DEPRESI TERHADAP KUALITAS HIDUP PENDERITA KUSTA DI RUMAH SAKIT LEPRA DAMIAN LEWOLEBA - Mukin, Yohanes Matius Demo; Buntoro, Ika Febianti; Indriarini, Desi; Setiono, Kresnawati Wahyu (Universitas Nusa Cendana, 2022)
Background : Leprosy is a infectious disease caused by Mycobacterium leprae. Leprosy provides physical impact such as disability and psychosicial impact like depression that affect to quality of life leprosy patient. Objective : To know the correlation between disability and depression level with quality of life leprosy patient in Hospital of Leprosy Damian Lewoleba Methods : This research use observational analytical method with cross sectional approach and the sample consisted of 30 patients. Sampling technique used was total sampling. Result : The result of univaraite analysis obtained 63,3 % of leprosy patient with disability level 0, 16,7 % of leprosy patient with disability level 1 and 20,0 % leprosy patient with disability level 2. Also found 3,3 % leprosy patient not depressed, 63,4 % mild depression and 33,3 % moderate depression. For quality of life found 36,7 % good quality and 63,3 % poor quality. Data was analyzed using Spearman Rank test and obtained the value p = 0,008 and p = 0,019. Conclusion : There was a correlation between disability and depression level with quality of life leprosy patientd. The prevention of disability and mental therapy should be improved quality of life leprosy patient.